Prenatal Protein Malnutrition Leads to Hemispheric Differences in the Extracellular Concentrations of Norepinephrine, Dopamine and Serotonin in the Medial Prefrontal Cortex of Adult Rats - Mokler, David J.; McGaughy, Jill A.; Bass, Donna; Morgane, Peter J.; Rosene, Douglas L.; Amaral, Ana C.; Rushmore, R. Jarrett; Galler, Janina R. (Frontiers in Neuroscience, 2019)
Exposure to prenatal protein malnutrition (PPM) leads to a reprogramming of the brain, altering executive functions involving the prefrontal cortex (PFC). In this study we used in vivo microdialysis to assess the effects of PPM on extracellular concentrations of norepinephrine (NE), dopamine (DA) and serotonin (5-HT) bilaterally in the ventral portion of the medial prefrontal cortex (vmPFC; ventral prelimbic and infralimbic cortices) of adult Long-Evans rats. Female Long-Evans rats were fed either a low protein (6%) or adequate protein diet (25%) prior to mating and throughout pregnancy. At birth, all litters were culled and fostered to dams fed a 25% (adequate) protein diet. At 120 days of age, 2 mm microdialysis probes were placed into left and right vmPFC. Basal extracellular concentrations of NE, DA, and 5-HT were determined over a 1-h period using HPLC. In rats exposed to PPM there was a decrease in extracellular concentrations of NE and DA in the right vmPFC and an increase in the extracellular concentration of 5-HT in the left vmPFC compared to controls (prenatally malnourished: N = 10, well-nourished: N = 20). Assessment of the cerebral laterality of extracellular neurotransmitters in the vmPFC showed that prenatally malnourished animals had a significant shift in laterality from the right to the left hemisphere for NE and DA but not for serotonin. In a related study, these animals showed cognitive inflexibility in an attentional task. In animals in the current study, NE levels in the right vmPFC of well-nourished animals correlated positively with performance in an attention task, while 5-HT in the left vmPFC of well-nourished rats correlated negatively with performance. These data, in addition to previously published studies, suggest a long-term reprogramming of the vmPFC in rats exposed to PPM which may contribute to attention deficits observed in adult animals exposed to PPM.